Covalent organic frameworks for optical applications. Issue 3 (22nd January 2021) - Zhang, Liang; Yi, Lezhi; Sun, Zhi‐Jun; Deng, Hexiang
Abstract: Linking molecules into extended crystalline networks to construct covalent organic frameworks (COFs) added in variety to the readily thriving research on molecule‐based solid‐state materials, featured by classic polymers and molecular crystals. Compared to the development of COFs for gas separation, energy storage, and conversion, where the porosity feature of COFs is utilized, the optical applications, such as fluorescence, white light emission, and photodynamic therapy, involving the molecular and crystalline feature of COFs, are much less explored. In this review, we focused on the optical properties of COFs, and how do these macroscopic properties correlate with the microscopic structure of COFs. Other than the influence from organic functional groups in previous reviews on COFs, here, three critical structure factors, the connection, orientation, and alignment of the molecular building blocks, are outlined and associated with the optical properties of COFs. We also analyze the properties of COFs from both energy and dynamic aspects in an attempt to provide further insight into the possible underlying mechanism. At the end of this review, we also discuss the remaining challenges and future directions for the design of COFs for optical applications, and unveil the potential of COFs toward this direction. Abstract : In this review, we focus on the impact from geometric arrangement of molecular building blocks within COF backbone, which is closely associated with the optical property. Specifically, three critical structure factors, the connection, orientation and alignment (C, O and A ) are extracted to facilitate the understanding of influence from microscopic structure features to their optical behaviors at macroscopic level.